1976
DOI: 10.1128/jb.127.2.934-940.1976
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol sensitivity of sporulation in Bacillus subtilis: a new tool for the analysis of the sporulation process

Abstract: The growth rate of Bacillus subtilis is lowered but the final cell yield is unchanged when certain concentrations of ethanol are present in the culture medium. At the concentration allowing growth at half-maximal rate, practically no spores are formed. Blockage of spore formation generally occurs at stage 0-I. Sensitivity to ethanol of the capacity to form spores is limited, in a nonsynchronized culture, to a period of at most 45 min around t1. Postexponential events such as excretion of certain enzymes and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…It was shown previously that the efficiency of spore formation was reduced more than 100-fold by alcohol stress (Bohin et al, 1976). Our results demonstrate that the s B -dependent pathway for spo0E induction is active upon ethanol stress in the wild type but can be replaced by secondary regulatory mechanisms in the sigB mutant strain (Fig.…”
Section: Ethanol Stress and The Physiological Relevance Of S B -Depensupporting
confidence: 72%
See 1 more Smart Citation
“…It was shown previously that the efficiency of spore formation was reduced more than 100-fold by alcohol stress (Bohin et al, 1976). Our results demonstrate that the s B -dependent pathway for spo0E induction is active upon ethanol stress in the wild type but can be replaced by secondary regulatory mechanisms in the sigB mutant strain (Fig.…”
Section: Ethanol Stress and The Physiological Relevance Of S B -Depensupporting
confidence: 72%
“…More than 30 years ago Bohin and colleagues (1976) reported that exponentially growing B. subtilis cells stressed with sub-inhibitory concentrations of short chain aliphatic alcohols ranging from C1 to C4 grow at a reduced rate but to the same final optical densities compared with unstressed cells. However, the efficiency of spore formation was reduced more than 100-fold (Bohin et al, 1976). In this context Gottig and colleagues (2005) isolated two suppressor mutations located in the rapA and sinR genes, whereas only the double mutant was completely resistant to inhibition of sporulation by alcohol stress.…”
Section: Ethanol Stress and Impairment Of Sporulation Specific Transcmentioning
confidence: 99%
“…Comparison of the growth characteristics of B. subtilis cultivated in media containing (1) glucose, (2) ribose and (3) glucose:ribose (1:1 combination) (Table 1) showed that cells grown on glucose had a slightly higher growth rate compared with cultures supplemented with ribose or a combination of glucose:ribose. Osadchaya et al (1997) found a correlation between growth rate and spore yield, which has also been described previously by Bohin et al (1976). In the latter study, the growth rate of B. subtilis was decreased by the addition of ethanol, which resulted in the same biomass being produced but a lower spore yield.…”
Section: Figsupporting
confidence: 75%
“…However, many more phase-bright spores were observed free and especially within cells in the control culture. Bohin et al (1976) found that a concentration of ethanol that reduced the growth rate, but not the final yield, of B. subtilzs vegetative cells in growth medium completely prevented sporulation. They attributed this activity of ethanol to its action on the cell membrane.…”
Section: Effects Of Chg On Spore Developmentmentioning
confidence: 95%
“…Stage IV, V and VI mutants have been employed previously (Power et al 1988;Shaker et al 1988) to help elucidate the stage of sporulation conferring resistance on a sporulating vegetative cell to various chemical disinfectant agents (Russell 1990). Bohin et al (1976) and Bohin and Lubochinsky (1982) reported that the growth rate of B. subtilis vegetative cells was reduced, and the final yield was unchanged when an appropriate concentration of ethanol was present in the culture medium. For example, 0-7 mol 1-' ethanol reduced the growth rate of approximately 50% of the normal rate; at this concentration, virtually no spores were formed.…”
Section: Introductionmentioning
confidence: 99%